Pengaruh Pendapatan Asli Daerah Dan Pendapatan Transfer Terhadap Kinerja Keuangan Pemerintah Daerah Provinsi Jawa Timur (International Forum of Researchers and Lecturers, 2024)
This research aims to examine the influence of Regional Original Income, General Allocation Funds and Special Allocation Funds on Regional Government Financial Performance. Using 38 samples of Regional Revenue and Expenditure Budget Realization Reports (APBD) for Regency/City Regional Governments in East Java Province for the 2020-2022 period which have been officially published and audited by the East Java Province Representative Financial Audit Agency (BPK Jatim). Testing was carried out using multiple regression. The test results prove that Regional Original Income has an influence on Regional Government Financial Performance. General Allocation Funds and Special Allocation Funds have no effect on Regional Government Financial Performance.